Hepatoprotective Potential Of Temu Kunci Ethanol Extract In Increasing Glutathione In Paracetamol-Induced Rats - Mawandha Sari Harahap; Desni Rinanda Silitonga; Chindy Umaya (Asosiasi Riset Ilmu Kesehatan Indonesia, 2025)
Liver damage induced by hepatotoxic compounds such as N-acetyl-p-aminophenol (N-APAP) remains a significant global health concern. Hepatotoxicity caused by N-APAP, particularly in cases of overdose or prolonged use, can lead to a reduction in glutathione levels in the liver, resulting in oxidative stress and cellular damage. This condition contributes to an increased incidence of liver diseases, including toxic hepatitis and acute liver failure, which can lead to serious complications and even death. Although various pharmacological therapies, such as N-acetylcysteine (NAC), are available to address N-APAP-induced liver damage, limitations such as side effects, high costs, and variable efficacy have driven the search for safer and more affordable therapeutic alternatives. Therefore, research on natural hepatoprotective agents, such as extracts from the rhizomes of fingerroot (Boesenbergia rotunda), has become increasingly relevant in addressing this issue. The aim of this study was to evaluate the hepatoprotective potential of ethanol extract from fingerroot rhizomes (Boesenbergia rotunda) in protecting the liver from N-acetyl-p-aminophenol (N-APAP)-induced damage. Specifically, this research focuses on measuring glutathione levels as a key indicator of the liver's protective mechanism against oxidative stress. In this study, 30 male White rats were randomly divided into six groups, each consisting of five rats. All rats were orally administered the extract at predetermined doses for 10 consecutive days, except for the negative and positive control groups. On the 10th day, all groups (except group 1) were treated with paracetamol (800 mg/kg body weight) to induce liver damage. Twenty-four hours after induction, the rats were sacrificed and liver samples were collected. Glutathione levels were measured using the ELISA immunosorbent assay. Statistical analysis showed that administering the ethanol extract of Fingerroot rhizomes (EERTK) for 10 days prior to N-APAP induction significantly increased the average antioxidant enzyme GSH-Px levels in the liver homogenate of rats in the EERTK 250 mg/kg BW (43.36 ± 1.34 U/mg protein), EERTK 500 mg/kg BW (55.70 ± 2.15 U/mg protein), and 750 mg/kg BW (53.14 ± 2.57 U/mg protein) group compared to the negative control group (N-APAP 800 mg/kg BW), which had the lowest average antioxidant enzyme GSH-Px level (33.86 ± 3.52 U/mg protein).